Ratios of torques of antagonist muscle groups in female soccer players - Struzik, A.; Pietraszewski, B.; Bober, T.; Siemienski, A. (Acta of Bioengineering and Biomechanics, 2018)
Purpose: An increase in the value of the hamstring-to-quadriceps (H/Q) ratio with an increase in angular velocity may effectively prevent injuries of the back of the thigh. Previous studies have found that the conventional H/Q ratio was unaltered along with an increasing angular velocity in females. Therefore, this study aimed to investigate the relationships between the conventional H/Q ratio and angular velocity in a group of female soccer players. Methods: The study was carried out on a group of 16 female soccer players (age: 20.7 ± 3.9 years, body height: 166.1 ± 5.8 cm, body mass: 58.4 ± 6.2 kg, training experience: 8.8 ± 4.1 years). Measurements of peak torque of extensors and flexors of the knee joint under static conditions and under isokinetic conditions (at angular velocities of 30°/s, 60°/s, 90°/s and 120°/s) were carried out using a Biodex dynamometer. Results: There was a statistically significant increase in the conventional H/Q ratio with an increase in angular velocity. These differences occurred between measurements at angular velocities of 0°/s and 30°/s, and 30°/s and 60°/s. Conclusions: As previously found for males, an increase in conventional H/Q ratio with increased angular velocity was also present in this group of female players. This phenomenon should reduce the number of injuries of the muscles of back of the thigh. Coaches should pay attention to increasing the level of strength in the group of knee joint flexor muscles so as to make the value of the H/Q ratio appropriately high and increasing with increasing angular velocity.